2014
DOI: 10.1073/pnas.1324233111
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome proliferator-activated receptor δ promotes colonic inflammation and tumor growth

Abstract: Although epidemiologic and experimental evidence strongly implicates chronic inflammation and dietary fats as risk factors for cancer, the mechanisms underlying their contribution to carcinogenesis are poorly understood. Here we present genetic evidence demonstrating that deletion of peroxisome proliferator-activated receptor δ (PPARδ) attenuates colonic inflammation and colitis-associated adenoma formation/growth. Importantly, PPARδ is required for dextran sodium sulfate induction of proinflammatory mediators… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
74
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(78 citation statements)
references
References 45 publications
3
74
0
1
Order By: Relevance
“…These receptors modulate many critical cellular functions, including fatty acid metabolism, wound healing, apoptosis, and inflammation. Therefore, PPARD could be involved in the development of several chronic diseases like diabetes (Villegas et al, 2011), cardiovascular disease (Skogsberg et al, 2003b;Lee et al, 2003), and cancer (Glinghammar et al, 2003;Peters et al, 2011;Ticha et al, 2013;Wang et al, 2014;Yang et al, 2014;Nath and Chan, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These receptors modulate many critical cellular functions, including fatty acid metabolism, wound healing, apoptosis, and inflammation. Therefore, PPARD could be involved in the development of several chronic diseases like diabetes (Villegas et al, 2011), cardiovascular disease (Skogsberg et al, 2003b;Lee et al, 2003), and cancer (Glinghammar et al, 2003;Peters et al, 2011;Ticha et al, 2013;Wang et al, 2014;Yang et al, 2014;Nath and Chan, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of CRC is complex and still not fully understood. However, it has been reported that genetic susceptibility to CRC is associated with genes related to cell proliferation, differentiation, and transformation, causing failure of apoptosis and abnormalities in multiple signaling pathways (Fearon and Vogelstein, 1990;Ticha et al, 2013;Wang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of this TFBS created by one SNP allele and not the other may in part be the reason for its association with intracerebral hemorrhages in Han Chinese [14]. PPARδ promotes inflammation and tumor growth [47] and an increase in HDL-c concentration in cardiovascular disease [48]. The…”
Section: Discussionmentioning
confidence: 99%
“…A recent report indicated that deletion of PPARδ in intestinal epithelial cells did not affect tumor incidence in AOM/DSS-treated mice [44] . Our recent results revealed that loss of PPARδ by deletion of its exons 4–5 attenuated chronic colonic inflammation and colitis-associated adenoma formation and growth with a reduction of certain pro-inflammatory mediators, including chemokines/cytokines, COX-2, and PGE 2 in both DSS-treated Apc Min/+ mice and AOM-treated Il-10 −/− mice [45] . In this study, we also found that PPARδ activation induced COX-2 expression in colonic tumor epithelial cells.…”
mentioning
confidence: 99%